2011
DOI: 10.1063/1.3515301
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of protonated leucine-enkephalin in the VUV range of 8–40 eV

Abstract: Until now, photodissociation studies on free complex protonated peptides were limited to the UV wavelength range accessible by intense lasers. We have studied photodissociation of gas-phase protonated leucine-enkephalin cations for vacuum ultraviolet (VUV) photons energies ranging from 8 to 40 eV. We report time-of-flight mass spectra of the photofragments and various photofragmentyields as a function of photon energy. For sub-ionization energies our results are in line with existing studies on UV photodissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
127
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(146 citation statements)
references
References 45 publications
18
127
1
Order By: Relevance
“…Experiments using VUV synchrotron radiation confirms that below the ionization threshold mainly a/x-species are formed [15]. The ionic abundances have been reported to increase with the photon energy, which is consistent with the shape of the photoabsorption cross section of the proteins.…”
Section: Results and Applicationssupporting
confidence: 66%
“…Experiments using VUV synchrotron radiation confirms that below the ionization threshold mainly a/x-species are formed [15]. The ionic abundances have been reported to increase with the photon energy, which is consistent with the shape of the photoabsorption cross section of the proteins.…”
Section: Results and Applicationssupporting
confidence: 66%
“…Different regimes of dissociation processes, below and above ionization energy (IE), have to be considered. For hνGIE, fragmentation is governed by IVR, while for hν9IE, the protonated peptide can be photoionized and a protonated leu-enk dication radical is formed, and the tyrosine side chain fragment in addition to immonium ions become the major fragments for photon energies exceeding 10 eV [44]. Note, however, that for multiply protonated proteins, photoionization is the main fragmentation pattern [31].…”
Section: Comparison With Protonated Peptidesmentioning
confidence: 99%
“…They have been in fast development during the last five years, mainly at SOLEIL in France and BESSY II in Germany. Different traps have been used: FT-ICR for the study of singly-charged atomic and small molecular ions as shown in this paper, linear traps for the study of singly-charged atomic ions [32], large molecular [9] and metallic clusters ions [8], RF trap for the study of large molecular ions of biological interest [33][34][35], electron beam ion trap (EBIT) for the study of highly-charged atomic ions [7,36]. To finish, let us note the construction of an electrostatic ring to store the ions at ASTRID II in Denmark, which will combine some of the advantages of both merged beam setup and ion trap.…”
Section: Resultsmentioning
confidence: 99%